Cultural Tourism as a Tool for Sustainable Development of Rural Areas (University of Maribor Press, 2022)
The monograph represents one of the results of the joint University of Maribor and University of Montenegro research groups in the frame of the bilateral project BI-ME_21-22-020, partially funded by Slovenian Research Agency ARRS and Montenegrin Ministry of Education, Science, Culture and Sports. In 6 chapters, it addresses the problem of uneven tourism development, which could be reduced by further development of cultural tourism. Both, Slovenia nad Montenegro, have rich and diverse cultural heritage, which represents an important tourism resource. Research conclusions show that the key to the future successful development of sustainable tourism in both countries lies in the design and upgrading of cultural tourism experiences. The monograph combines a range of authors, disciplines, approaches and methods, thus, proving once again that tourism is a very rich and diverse interdisciplinary field.